Runoff loss of nitrogen and phosphorus from a rice paddy field in the east of China: Effects of long-term chemical N fertilizer and organic manure applications - Cui, Naxin; Cai, Min; Zhang, Xu; Abdelhafez, Ahmed A.; Zhou, Li; Sun, Huifeng; Chen, Guifa; Zou, Guoyan; Zhou, Sheng (Global ecology and conservation, 2020)
Agrochemicals, e.g., nitrogen (N) and phosphorus (P) fertilizers are being used extensively to increase the agricultural production; however, considerable losses of these fertilizers find their way to the surrounding surface water bodies causing severe pollution and eutrophication. Such non-point source of pollution seemed to be more pronounced in the rice fields. Accordingly, a two-year (2018–2019) field study was conducted at a rice paddy field under long-term N fertilizer management practices in the rural suburb of Shanghai, China. N and P losses through the surface runoff in the paddy field were measured. Six N fertilizer practices were performed since 2011 as follows: no N treatment (N0), chemical N treatment (urea, N 46%) applied at the rates of 100 (N100), 200 (N200), 300 (N300) kg N ha−1 and combinations of chemical and organic N fertilizers (30% organic manure) at the rates of 200 (ON200) and 300 kg N ha−1 (ON300). Results showed that the highest runoff losses of TN (20.5 kg ha−1) and TP (1.66 kg ha−1) were respectively produced by N300 and ON300 practices during the rice growing season. TN runoff loss significantly decreased by reducing the rate of N fertilizer (P < 0.05). Comparing with N300 treatment, ON300, ON200 and N200 treatments reduced N loss by 2.4%, 27.0%, and 13.9% in 2018 and by 24.0%, 49.0% and 37.5% in 2019, respectively. Organic manure substitute decreased N loss but increased P loss from the surface runoff. The time period after fertilizer application significantly impacted N and P loss from surface runoff. The surface runoff occurring during the early stage after fertilizer applications contributed mostly to the total N loss. Consequently, the control of initial surface runoff events might be an effective strategy to attenuate the surrounding water pollution due to N surface runoff in the paddy fields. •Nitrogen (N) loss through surface runoff was decreased by reducing the rate of N fertilizer application.•Organic manure amendment decreased N loss but increased phosphorus (P) loss from the surface runoff.•The majority of N loss was NH4+-N in chemical N fertilizer treatments, while organic N was dominant in combined ones.•The time period after fertilizer application significantly impacted N and P loss from surface runoff.